Restoration of a Danube floodplain forest: what happens to species richness of terrestrial beetles?. Issue 4 (15th November 2017) - Gruppe, Axel; Kilg, Markus; Schopf, Reinhard
Abstract : Along the upper Danube, between river kilometer 2, 472 and 2, 464 (Bavaria, Germany), a managed hardwood forest was reconnected to the river via a newly carved floodplain channel. We report the stepwise alteration of the diversity of terrestrial beetles for six successive years from 2007 to 2012. In a 2‐year preliminary period (2007–2008), we recorded the baseline stage before the technical measures were implemented (2009–2010) and the onset of restoration occurred (2011–2012) with a continuous water flow in the new channel and seven flooding events. Each sample plot was equipped with a pitfall trap, an emergence photo‐eclector, an arboreal photo‐eclector, and a flight interception trap in breast height and in the canopy, respectively. The beetle communities act as an indicator to detect possible disturbance events when a riparian hardwood forest is stepwise transformed to become a new floodplain ecosystem. Within the 6‐year study period, we trapped 62, 107 individual beetles, representing 85 families, 544 genera, and 1, 191 species. Compared to the baseline stage, the abundance and the number of species decreased, including rare and red list species. On functional level, the species decline was particularly pronounced for zoophagous and mycetophagous species. Finally, we suppose that the 2‐year period since the launch of the new channel is too short for the establishment of a beetle community adjusted to the terrestrial part of the developing new floodplain forest.